(untitled) (Innovaciones Educativas, 2022)
The random variable and its probability distribution are fundamental concepts in statistical and probabilistic school education because they manifest in everyday experiences. Teaching them becomes a complex task due primarily to the difficulties associated with understanding them and the concept of function. Therefore, we proposed as a study objective to assess the random variable’s instruction process and its probability distribution in Chilean secondary education, based on the Theory of Didactic Situations (TSD) and the Theory of Registration of Semiotic Representations (TRRS). We designed a test containing a didactic situation applied to 10th-grade Chilean students (15 to 16 years old) with a qualitative perspective and a descriptive-interpretive approach. The findings showed that more than half of the students (64%) managed to identify and represent the random variable in verbal, figural, or tabular language, and a similar percentage (59%), its probability distribution. Concerning the TRRS, this could indicate that students are in the process of building both objects. Subsequently from the TSD, we observed the vital role that the teacher played in the phases of the said didactic situation. Studying didactic theories, we discovered that bringing complex objects to the classroom can help actual teachers and those being trained to look at their practice with more understructure to make it more accessible and understandable to their students.